The Rainmaker - Coppola, Francis Ford, 1939-; Damon, Matt; Danes, Claire, 1979-; Voight, Jon, 1938-; Grisham, John (Widescreen DVD collection., 1995)
A rookie lawyer in over his head on a high-profile case hires a feisty paralawyer who specializes in flunking the bar. Their chances of winning are slim to none until they uncover a trail of corruption.